2009
DOI: 10.1007/s12132-009-9069-6
|View full text |Cite
|
Sign up to set email alerts
|

Patterns of Residential Mobility Amongst Children in Greater Johannesburg–Soweto, South Africa: Observations from the Birth to Twenty Cohort

Abstract: Frequent residential movement challenges children to adapt to change, amongst others, houses and neighbourhoods, friends and schools, and this may have either or both negative and positive influences on their health and well-being. However, there is currently little knowledge of the patterns of child residential mobility within South Africa's urban environment. This paper uses address data of children in the Birth to Twenty cohort to analyse the frequencies and patterns of residential mobility observed over th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 12 publications
0
11
0
Order By: Relevance
“…It thus follows that adolescents who are changing residence as well as SES are likely to be those who are dealing with the most rapid exposure to new lifestyles that place them at greatest risk of obesity. Within the Bt20 study population, residential mobility is strongly linked to socioeconomic factors with movement found to be employed as a strategy to either improve children and families’ living circumstances, or to survive in challenging or prohibitive conditions ( Ginsburg et al, 2009, 2011 ). The present study highlights that in the case of mobility prompted by improved circumstances, there is the potential for adverse consequences.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It thus follows that adolescents who are changing residence as well as SES are likely to be those who are dealing with the most rapid exposure to new lifestyles that place them at greatest risk of obesity. Within the Bt20 study population, residential mobility is strongly linked to socioeconomic factors with movement found to be employed as a strategy to either improve children and families’ living circumstances, or to survive in challenging or prohibitive conditions ( Ginsburg et al, 2009, 2011 ). The present study highlights that in the case of mobility prompted by improved circumstances, there is the potential for adverse consequences.…”
Section: Discussionmentioning
confidence: 99%
“…The questionnaire aimed to verify all historical address records as correctly reflecting the children’s primary places of residence over the 15 year period, and to complete any missing or partial address information. The questionnaire data enabled the construction of a residential history for each child from birth to 15 years from which movements could be identified (see Ginsburg et al, 2009 for a more detailed description of the study of residential mobility within the cohort). During the course of this same year, anthropometric assessments of the cohort were also conducted.…”
Section: Methodsmentioning
confidence: 99%
“…For the Bt20 cohort apartheid legislation limited the neighbourhoods that population groups could reside in around the time of the cohort's birth, although the removal of this legislation very quickly led to children experiencing different environments. For example between birth and 14 years, 56% of the Black cohort children had moved their address at least once (Ginsburg et al, 2009). This means that by the time the children of the cohort were entering their adolescent years they were residing in very diverse neighbourhoods, with the potential to influence health in different ways.…”
Section: Introductionmentioning
confidence: 99%
“…This Residential Move Questionnaire (RMQ) was completed by 2158 members of the original residential cohort (66%), with the balance of 1115 cohort members identified as cases of study attrition. A more detailed account of the BT20 data collection processes and the development and implementation of the specific study of residential movement within the cohort can be found in Richter et al (2007) and Ginsburg et al (2009).…”
Section: Datamentioning
confidence: 99%
“…A preliminary analysis of the frequency of residential mobility within the BT20 cohort revealed that the majority of children (64%) had moved home at least once during their first 14 years, with the largest proportion of moves occurring within the Greater Johannesburg urban area (Ginsburg et al , 2009). The principal aim of this study is to model the occurrence of initial and repeated residential mobility of children in the cohort so as to identify factors associated with movement, relating to the child, the child's primary caregiver, and the child's household.…”
Section: Introductionmentioning
confidence: 99%